Web-Based Decision Support System for Prosperous Family Classification Using the Analytical Hierarchy Process - Andino Maseleno; Adi Prasetia Nanda; Rara Marselina Jupon; Eka Fitriana (Jurnal Studi Multidisiplin Ilmu, 2025)
Purpose: This study designs and implements a web-based Decision Support System (DSS) for classifying prosperous families in Dusun Cibanban, Desa Gerning, Tegineneng District, Pesawaran Regency, Indonesia, applying the Analytical Hierarchy Process (AHP). The work addresses the inefficiency and subjectivity of manual welfare assessment routines used by local administrators.Methodology: A design science research approach guided development, following the waterfall model through requirements analysis, design, implementation, testing, and deployment. AHP derived priority weights from pairwise comparisons among welfare criteria adapted from national family welfare standards, implemented using Personal Home Page (PHP) with CodeIgniter, JavaScript, and MySQL.Results: The system computed AHP priority weights for every household head across six welfare criteria and produced a ranked classification for 102 households. Black-box testing confirmed all primary modules operated without defects. The household head Marsidi obtained the highest composite score, 0.1736, with a criteria consistency ratio of 0.071, within Saaty's acceptable threshold.Conclusions: The system replaces a slow, subjective manual procedure with a faster, more transparent classification mechanism accessible through an ordinary browser.Limitations: The evaluation was confined to a single sub-village with 102 household heads, criteria weights rested on expert elicitation rather than empirical validation, and concurrency performance under production loads was not assessed. Contributions: The study offers a documented, replicable community-level AHP-DSS implementation that local administrators elsewhere in Indonesia can adapt for data-driven welfare targeting.